Additive agent for cationic asphalt emulsion
Patent Information
- Application Number
- JP2023129899
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
Smart Images

Figure 2025025275000001 
Figure 2025025275000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an additive for a cationic asphalt emulsion, a cationic asphalt emulsion composition and a method for producing the same, a coating layer and a method for applying the same, and a method for applying an asphalt pavement. [Background technology]
[0002] Asphalt is generally used in a liquid form by heating, but it is known that asphalt is sometimes emulsified in water so that it can be used at room temperature without heating. Such an emulsion is called asphalt emulsion.
[0003] In asphalt emulsions, asphalt is usually dispersed as fine particles in water containing an emulsifier. When asphalt emulsions are used by spraying or coating, the asphalt separates (decomposes) from the water, creating caking properties and exerting strength.
[0004] Asphalt emulsions are classified as cationic, anionic, or nonionic asphalt emulsions depending on the emulsifier used.
[0005] Cationic asphalt emulsions are used for penetration and mixing, and asphalt emulsions for penetration are known to be used as tack coats and prime coats. Tack coats are used to bond a newly laid asphalt mixture layer to the asphalt mixture layer below, or to improve adhesion to joints and structures. Prime coats are applied on top of the upper roadbed to stabilize the roadbed and to improve the compatibility between the roadbed and the asphalt mixture layer above it.
[0006] Cationic asphalt emulsions for tack coats include "PK-4" as specified in the Japanese Industrial Standards JIS K 2208 (2000), and for prime coats, "PK-3" as specified in the same standard. However, asphalt coatings formed using these asphalt emulsions are sticky, and therefore, particularly in the summer when the road surface temperature is high, there are problems such as asphalt adhering to the tires of construction machines, causing the coating to peel off from the construction surface, or asphalt adhering to the tires contaminating the road surface outside the construction site.
[0007] One asphalt emulsion that prevents this type of asphalt adhesion problem is "PKM-T," a tire adhesion prevention asphalt emulsion specified in the Japan Asphalt Emulsion Association standard JEAAS2011.
[0008] Patent Document 1 does not relate to a cationic asphalt emulsion, but describes an asphalt emulsion that contains conjugated diene polymer particles, an anionic or nonionic emulsifier, asphalt, a specific silane coupling agent, and an epoxy resin in order to suppress stickiness of asphalt.
[0009] Furthermore, Patent Document 2 describes a spray-type surface treatment method that does not use an excessive amount of binder, can firmly and stably bind aggregate to the road surface, can be applied at room temperature, and has a short curing time, and in order to provide a pavement with excellent durability and stability constructed by this treatment method, the method includes a step of spraying a binder made of a specific cationic asphalt emulsion and a decomposition assistant that promotes its decomposition at the same time or in succession, and a step of spraying aggregate. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2010-174229 A [Patent Document 2] JP 2000-336602 A Summary of the Invention [Problem to be solved by the invention]
[0011] As mentioned above, asphalt emulsions generally have the problem of asphalt adhesion after application, and "PKM-T" is known as a cationic asphalt emulsion that suppresses this problem. However, the problem of asphalt adhesion has not been fully resolved, and improvements in this area are required.
[0012] In order to solve the problem of asphalt adhesion in cationic asphalt emulsions, the present inventors added conjugated diene polymer particles as disclosed in Patent Document 1 to the cationic asphalt emulsion, but found that aggregates were generated in the emulsion. If the emulsion contains aggregates, the viscosity increases, and there is a risk of workability decreasing when spraying or applying as a tack coat or prime coat. In addition, as disclosed in Patent Document 2, a decomposer may be used to promote separation (decomposition) of asphalt from water during construction using a cationic asphalt emulsion, but when the emulsifier used to prepare the polymer particles in the cationic asphalt emulsion is anionic or nonionic, the decomposer is ineffective against the emulsifier in the cationic asphalt emulsion, resulting in problems with construction.
[0013] In view of the above-mentioned current situation, the present invention aims to provide an additive that, when added to a cationic asphalt emulsion, can provide a cationic asphalt emulsion composition that suppresses asphalt adhesion after construction, is effective in shortening the construction period by using a decomposer, and is less likely to produce agglomerates in the emulsion. [Means for solving the problem]
[0014] As a result of intensive research by the inventors to solve the above problems, they discovered that the above problems can be solved by adding polymer particles containing an acrylic rubber in which the emulsifier is composed only of a cationic emulsifier to a cationic asphalt emulsion, and thus arrived at the present invention.
[0015] That is, the present invention relates to an additive for a cationic asphalt emulsion, the additive comprising polymer particles, the polymer particles comprising an emulsifier and an acrylic rubber, and the emulsifier being composed only of a cationic emulsifier. Effect of the Invention
[0016] According to the present invention, it is possible to provide an additive that, when added to a cationic asphalt emulsion, can provide a cationic asphalt emulsion composition that inhibits asphalt adhesion after construction, is effective in shortening the construction period by using a decomposer, and is less likely to produce agglomerates in the emulsion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Hereinafter, an embodiment of the present invention will be described in detail. (Cationic asphalt emulsion additive) The cationic asphalt emulsion additive according to this embodiment contains at least polymer particles, the polymer particles contain an emulsifier and an acrylic rubber, and the emulsifier is composed only of a cationic emulsifier.
[0018] (Polymer particles) The polymer particles are composed of at least a cationic emulsifier and contain an acrylic rubber. By containing an acrylic rubber in the polymer particles, asphalt adhesion after application using an asphalt emulsion composition obtained by adding the polymer particles to a cationic asphalt emulsion can be suppressed. In addition, a decomposer that promotes decomposition of the asphalt emulsion composition is effective and does not impair the workability of application. In addition, agglomerates are unlikely to occur in the emulsion composition, and the workability when the emulsion composition is sprayed or applied can be improved. Furthermore, the emulsion composition has good adhesion to an adherend, particularly to an asphalt mixture layer, and peeling and slippage between asphalt mixture layers is unlikely to occur.
[0019] The acrylic rubber refers to a synthetic rubber mainly composed of an acrylic monomer. The acrylic monomer is not particularly limited, but examples thereof include acrylic acid alkyl esters such as ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, octyl acrylate, dodecyl acrylate, stearyl acrylate, and behenyl acrylate; aromatic ring-containing acrylates such as phenoxyethyl acrylate and benzyl acrylate; hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate; glycidyl acrylates such as glycidyl acrylate and glycidyl alkyl acrylate; and alkoxyalkyl acrylates. Among these, acrylic acid alkyl esters are preferred, and butyl acrylate is particularly preferred.
[0020] The content of the acrylic rubber in the polymer particles is not particularly limited as long as it exceeds 0% by weight, but from the viewpoint of particularly suppressing asphalt adhesion after application and maintaining appropriate flexibility of the coating layer applied by application, it is preferably 30 to 80% by weight, more preferably 30 to 60% by weight, and even more preferably 35 to 55% by weight. If it is less than 30% by weight, the coating layer applied by application may become too hard.
[0021] The acrylic rubber may or may not be used in combination with a monomer other than the acrylic monomer. Examples of the monomer other than the acrylic monomer include methacrylic monomers, aromatic vinyl compounds such as styrene, vinyl cyanide compounds such as acrylonitrile, vinyl halide compounds such as vinyl chloride, vinyl acetate, and alkenes such as ethylene, propylene, and butadiene.
[0022] The ratio of the acrylic monomer to the entire acrylic rubber is preferably 50% by weight or more, more preferably 70% by weight or more, further preferably 80% by weight or more, and particularly preferably 90% by weight or more.
[0023] The acrylic rubber has a crosslinked structure. To introduce the crosslinked structure, for example, a crosslinkable monomer such as a polyfunctional monomer may be used when synthesizing the acrylic rubber by polymerizing the monomer components.
[0024] Examples of the polyfunctional monomer include allyl (meth)acrylate, allyl alkyl (meth)acrylate, allyloxy alkyl (meth)acrylates, polyfunctional (meth)acrylates having two or more (meth)acrylic groups such as polyethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, and divinylbenzene. Preferred are allyl methacrylate, triallyl isocyanurate, butanediol di(meth)acrylate, and divinylbenzene, and particularly preferred is allyl methacrylate.
[0025] The amount of the polyfunctional monomer used may be within a known range and is not particularly limited. For example, the amount may be 0.01 to 10 parts by weight, preferably 0.05 to 5 parts by weight, and more preferably 0.1 to 3 parts by weight, relative to 100 parts by weight of the total of the monomer components (monomers other than the polyfunctional monomer) constituting the acrylic rubber.
[0026] The acrylic rubber may be composed of a single rubber composition, or may be composed of a plurality of rubbers each having a different type or amount of monomer and / or crosslinkable monomer.
[0027] (Core layer and shell layer) The polymer particles may be composed only of the acrylic rubber. However, it is preferable that the acrylic rubber is used as a core layer and further includes a shell layer located on the outside of the core layer, because when the polymer particles are added to a cationic asphalt emulsion, agglomerates are less likely to occur, the polymer particles are more likely to be uniformly dispersed in the emulsion, and asphalt adhesion after application of the emulsion composition can be more effectively suppressed. The shell layer is preferably composed of a non-crosslinked polymer, not a rubber. The non-crosslinked polymer refers to a polymer that does not include a crosslinked structure.
[0028] The shell layer refers to a polymer layer located on the surface side of the polymer particle, and is also called a graft layer. The shell layer is preferably graft-bonded to the core layer. However, the polymer of the shell layer also includes a polymer that is not graft-bonded to the core layer. The shell layer covers the surface of the core layer, but is not limited to covering the entire surface of the core layer, and it is sufficient that the shell layer covers at least a part of the surface of the core layer.
[0029] The monomer constituting the non-crosslinked polymer of the shell layer is not particularly limited, and examples thereof include (meth)acrylic monomers, aromatic vinyl monomers, etc. In the present application, the term "(meth)acrylic" is used to collectively refer to acrylic and methacrylic.
[0030] The (meth)acrylic monomer is not particularly limited, and examples thereof include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate; aromatic ring-containing (meth)acrylates such as phenoxyethyl (meth)acrylate and benzyl (meth)acrylate; hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate; glycidyl (meth)acrylates such as glycidyl (meth)acrylate and glycidyl alkyl (meth)acrylate; alkoxy (meth)alkyl acrylates; (meth)acrylonitrile, substituted (meth)acrylonitrile, (meth)acryloamide, 2-(dimethylamino)ethyl (meth)acrylate, and polyethylene glycol mono(meth)acrylate. Among these, (meth)acrylic acid alkyl esters are preferred, and methacrylic acid alkyl esters are particularly preferred.
[0031] The aromatic vinyl monomer is not particularly limited, and examples thereof include unsubstituted vinyl aromatic compounds such as styrene and 2-vinylnaphthalene; substituted vinyl aromatic compounds such as α-methylstyrene; ring-alkylated vinyl aromatic compounds such as 3-methylstyrene, 4-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,5-dimethylstyrene, and 2,4,6-trimethylstyrene; ring-alkoxylated vinyl aromatic compounds such as 4-methoxystyrene and 4-ethoxystyrene; ring-halogenated vinyl aromatic compounds such as 2-chlorostyrene and 3-chlorostyrene; ring-ester-substituted vinyl aromatic compounds such as 4-acetoxystyrene; and ring-hydroxylated vinyl aromatic compounds such as 4-hydroxystyrene. Among them, substituted or unsubstituted styrene is preferred, styrene and / or α-methylstyrene is more preferred, and styrene is particularly preferred. The aromatic vinyl monomer may be used alone or in combination of two or more.
[0032] As the monomer constituting the non-crosslinked polymer of the shell layer, it is preferable to use at least one selected from the group consisting of acrylic monomers, methacrylic monomers, and aromatic vinyl monomers.
[0033] From the viewpoint of suppressing adhesion of asphalt, it is preferable to use at least a methacrylic monomer and / or an aromatic vinyl monomer as a monomer constituting the polymer of the shell layer. In this case, the total amount of the methacrylic monomer and the aromatic vinyl monomer among the whole monomers constituting the polymer of the shell layer is preferably 40 to 100% by weight, more preferably 60 to 100% by weight, further preferably 80 to 100% by weight, and particularly preferably 90 to 100% by weight.
[0034] In addition, it is preferable to use at least a methacrylic monomer as a monomer constituting the polymer of the shell layer so that the emulsion composition obtained by adding the polymer particles to the cationic asphalt emulsion can maintain stability for a long period of time. In addition, it is possible to use only a methacrylic monomer as a monomer constituting the polymer of the shell layer, but from the viewpoint of imparting polymerization stability, it is more preferable to use a methacrylic monomer and an aromatic vinyl monomer in combination.
[0035] From the above viewpoints, the total amount of methacrylic monomers among all the monomers constituting the polymer of the shell layer is preferably 40 to 100% by weight, more preferably 60 to 99% by weight, even more preferably 80 to 98% by weight, and particularly preferably 90 to 97% by weight.
[0036] The non-crosslinked polymer forming the shell layer is preferably a polymer exhibiting a glass transition temperature (Tg) of -25°C or higher, more preferably -10°C or higher, even more preferably 0°C or higher, even more preferably 20°C or higher, particularly preferably 40°C or higher, and most preferably 50°C or higher, so as to further suppress asphalt adhesion after application of the emulsion composition. Furthermore, it may be 60°C or higher, 70°C or higher, 80°C or higher, or 90°C or higher. In addition, the higher the glass transition temperature of the polymer of the shell layer, the more advantageously the emulsion composition obtained by adding the polymer particles to the cationic asphalt emulsion can maintain stability for a long period of time. The upper limit of the glass transition temperature of the polymer of the shell layer is not particularly limited, but may be, for example, 120°C or lower, or 110°C or lower.
[0037] The glass transition temperature of the non-crosslinked polymer forming the shell layer can be controlled by changing the type and ratio of the monomers constituting the polymer. For example, by using at least a methacrylic monomer and / or an aromatic vinyl monomer as the monomer constituting the polymer of the shell layer, it is possible to increase the glass transition temperature of the polymer.
[0038] The glass transition temperature can be determined by the following FOX formula. FOX formula: 1 / (Tg(K))=Σ(Mi / Tgi) (In the formula, Mi represents the weight fraction of monomer i constituting the polymer, and Tgi represents the glass transition temperature (K) of the homopolymer of monomer i.)
[0039] The glass transition temperature of the homopolymer can be determined using the glass transition temperature (Tg) described in POLYMER HANDBOOK-FOURTH EDITION- (J. Brandrup et al.).
[0040] (Core layer content) In an embodiment in which the polymer particles include a core layer and a shell layer, the content of the core layer in the polymer particles is not particularly limited and may be, for example, 20 to 90% by weight. However, from the viewpoint of being able to particularly suppress asphalt adhesion after construction and maintaining a suitable flexibility of the coating layer provided by construction, it is preferably 30 to 80% by weight, more preferably 30 to 60% by weight, even more preferably 35 to 60% by weight, and particularly preferably 35 to 55% by weight. If it is less than 30% by weight, the coating layer provided by construction may become too hard.
[0041] In addition, when the polymer particles have a shell layer, they may further have an intermediate layer between the core layer and the shell layer as long as the effects of the invention are achieved. The intermediate layer is a layer composed of a polymer and is preferably graft-bonded to the core layer. When such an intermediate layer is present, the intermediate layer covers at least a part of the surface of the core layer, and the shell layer covers at least a part of the surface of the intermediate layer.
[0042] (Volume average particle size of polymer particles) The particle size of the polymer particles is not particularly limited, and may be, for example, a volume average particle size of about 10 to 1000 nm. However, from the viewpoints of workability during spraying or coating, productivity, stability of the polymerization system, stability of the emulsion composition, etc., the volume average particle size is preferably 80 to 500 nm, more preferably 100 to 400 nm, and even more preferably 150 to 350 nm. The volume average particle size of the polymer particles is measured using a particle size measuring device in the state of the polymer particles in latex. The particle size of the polymer particles can be controlled by the type and amount of the polymerization initiator, chain transfer agent, redox agent, emulsifier, etc. used during polymerization, polymerization temperature, polymerization time, etc.
[0043] (Method of Producing Polymer Particles) The method for producing the polymer particles is not particularly limited, but for example, emulsion polymerization, mini-emulsion polymerization, micro-emulsion polymerization, and emulsifier-free (soap-free) emulsion polymerization can be used.
[0044] Generally, emulsifiers used in emulsion polymerization include nonionic emulsifiers (nonionic surfactants), anionic emulsifiers (anionic surfactants), cationic emulsifiers (cationic surfactants), amphoteric surfactants, and the like. However, since the obtained polymer particles may contain emulsifiers other than cationic emulsifiers, it is preferable to use only cationic emulsifiers (cationic surfactants) as the emulsifiers used in the emulsion polymerization of the present disclosure.
[0045] The cationic emulsifier (cationic surfactant) is not particularly limited, and examples thereof include the following compounds: alkylamine salts such as alkylamine acetates and alkyltrimethylenediamine adipates; and quaternary ammonium salts such as alkyltrimethylammonium chloride, distearyldimethylammonium chloride, and alkylbenzyldimethylammonium chloride. Examples of alkylamine acetates include coconut amine acetate, stearylamine acetate, octadecylamine acetate, and tetradecylamine acetate, and examples of alkyltrimethylammonium chlorides include lauryltrimethylammonium chloride, stearyltrimethylammonium chloride, cetyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, and behenyltrimethylammonium chloride.
[0046] These emulsifiers may be used alone or in combination of two or more. Among the emulsifiers, an emulsifier containing alkyltrimethylammonium chloride is preferred from the viewpoint of excellent polymerization stability.
[0047] When the emulsion polymerization method is employed, known polymerization initiators, i.e., azo-based initiators, hydrogen peroxide, potassium persulfate, ammonium persulfate, etc., can be used as thermal decomposition initiators. Among these, azo-based initiators such as 2,2'-azobis(2-methylpropionamidine) dihydrochloride are preferred.
[0048] The solvent used during emulsion polymerization may be any solvent that allows the emulsion polymerization to proceed stably, and for example, water can be suitably used.
[0049] The temperature during emulsion polymerization is not particularly limited as long as the emulsifier is uniformly dissolved in the solvent, but is, for example, 40 to 75°C, preferably 45 to 70°C, and more preferably 49 to 65°C.
[0050] When the polymer particles are produced by emulsion polymerization, for example, a latex of the polymer particles may be spray-dried to obtain a powder that can be redispersed in water, and this powder may be used as the polymer particles.
[0051] The additive for cationic asphalt emulsion according to the present embodiment may be in the form of a latex of the polymer particles or in the form of a powder of the polymer particles. The additive is preferably in the form of a latex of the polymer particles because it has excellent dispersibility in the cationic asphalt emulsion.
[0052] (Cationic asphalt emulsion) In this disclosure, a cationic asphalt emulsion refers to an emulsion that includes at least asphalt, water, and a cationic emulsifier.
[0053] The cationic asphalt emulsion is not particularly limited, but examples thereof include "PK-1", "PK-2", "PK-3", "PK-4", "MK-1", "MK-2", and "MK-3" as specified in the Japanese Industrial Standard JIS K 2208 (2000); and "PK-P", "PK-H", "MK-C", "PKM-T", "PKR-T", "PKR-S-1", and "PKR-S-2" as specified in the Japan Asphalt Emulsion Association Standard JEAAS-2006.
[0054] In particular, it is preferable to use the additive according to the present disclosure for the cationic asphalt emulsions "PK-4", "PKM-T" and "PKR-T" for tack coat. Among them, "PKM-T" is a tire adhesion inhibiting asphalt emulsion, and according to the present disclosure, the tire adhesion inhibiting effect of "PKM-T" can be further improved.
[0055] The asphalt contained in the cationic asphalt emulsion is not particularly limited, and examples thereof include natural asphalt such as lake asphalt, rock asphalt, asphaltite, etc., petroleum asphalt such as straight asphalt, blown asphalt, etc., semi-blown asphalt, hard asphalt, etc. In addition, modified asphalt obtained by modifying these asphalts by blending thermosetting resins, thermoplastic resins, rubber, etc. may be used.
[0056] The cationic asphalt emulsion can be produced by a conventional method, and is not particularly limited, but for example, it can be produced by emulsifying a mixture of asphalt, amines, and a weak acid (e.g., an organic acid such as acetic acid) or a strong acid (e.g., an inorganic acid such as hydrochloric acid or amidosulfuric acid) using a colloid mill or homogenizer. Examples of the amines include primary amines, secondary amines, tertiary amines, quaternary ammonium salts, polyamines, and mixed amines thereof.
[0057] (Cationic asphalt emulsion composition) The cationic asphalt emulsion composition of the present disclosure contains a cationic asphalt emulsion and the additive. The additive according to the present disclosure can be used by adding and mixing it with the cationic asphalt emulsion to disperse the polymer particles, and the polymer particles of the additive according to the present disclosure dispersed in the cationic asphalt emulsion are called a cationic asphalt emulsion composition. The cationic asphalt emulsion composition according to the present disclosure not only suppresses adhesion of asphalt after application to the target object, but also prevents agglomerates from forming in the composition, improving workability when spraying or applying. In addition, the use of a decomposer, particularly an anionic decomposer, is effective in shortening the application period.
[0058] The content of the additive in the cationic asphalt emulsion composition can be appropriately adjusted in consideration of the effects of the invention, but from the viewpoint of particularly excellent improvement effects of the cationic asphalt emulsion, for example, the solid content equivalent of the polymer particles is preferably in the range of 1 to 50 parts by weight, more preferably 1 to 40 parts by weight, and even more preferably 3 to 30 parts by weight, per 100 parts by weight of the solid content equivalent of the cationic asphalt emulsion. If it exceeds 50 parts by weight, the cost may be higher than the improvement effect of the cationic asphalt emulsion for the increased amount.
[0059] The method of including the additives in the cationic asphalt emulsion composition and the method of mixing the additives into the cationic asphalt emulsion are not particularly limited, and any well-known mixing method can be appropriately applied.
[0060] The cationic asphalt emulsion composition according to the present disclosure may further contain components other than the cationic asphalt emulsion and the additive according to the present disclosure. Such other components are not particularly limited, but may include, for example, organic solvents such as aliphatic hydrocarbons and aromatic hydrocarbons, aggregates such as silica, defoamers, emulsifiers, and flow agents.
[0061] The use of the cationic asphalt emulsion composition according to the present disclosure is not particularly limited, and may be for penetration or mixing, but is preferably for penetration. Specific examples of the use for penetration include warm season penetration, cold season penetration, surface treatment, prime coat, cement stabilization layer curing, tack coat, etc.
[0062] The cationic asphalt emulsion composition according to the present disclosure has excellent adhesion to an adherend, particularly to an asphalt mixture layer, and therefore can be suitably used for a tack coat or a primer coat. In particular, since it has excellent adhesion between asphalt mixture layers, which is required for a tack coat, it can be particularly suitably used for a tack coat.
[0063] The asphalt mixture layer is a layer formed by an asphalt mixture, and the asphalt mixture refers to a mixture consisting of asphalt and other materials. Examples of other materials include coarse aggregate, fine aggregate, and filler. Examples of asphalt mixtures include heated asphalt mixtures in which asphalt, coarse aggregate, fine aggregate, and filler are mixed and heated at, for example, 160 to 200 ° C., and room temperature asphalt mixtures in which asphalt, coarse aggregate, fine aggregate, and filler are mixed with an asphalt emulsion and applied at, for example, 100 ° C. or less. However, in order to achieve the effects of the invention of the present disclosure, the cationic asphalt emulsion composition according to the present disclosure must be used at a temperature that does not exceed the glass transition temperature of the polymer particles contained therein, particularly the non-crosslinked polymer of the shell layer. In addition, when at least one of the asphalt mixture layers is a layer formed by a heated asphalt mixture, the heated asphalt mixture is limited to a temperature that does not exceed the glass transition temperature of the polymer particles contained therein after heating and application. The use temperature of the cationic asphalt emulsion composition according to the present disclosure varies depending on the components constituting the polymer particles, but specifically, for example, it may be 80° C. or lower, or 70° C. or lower.
[0064] The tack coat is a coat that is mainly sprayed or applied on a newly laid asphalt mixture layer to achieve interlayer adhesion between the latter and the asphalt mixture layer below, or is used to improve adhesion between the asphalt mixture layer and joints or structures. The primer coat is mainly sprayed or applied on the upper roadbed to stabilize the upper roadbed and improve the compatibility between the upper roadbed and the asphalt mixture layer above it.
[0065] The cationic asphalt emulsion composition according to the present disclosure can be used by spraying or applying it to an object. The method of spraying or applying is not particularly limited and can be a known method, for example, spraying using a sprayer such as a distributor (vehicle for spraying asphalt emulsion) or an engine sprayer, a watering can, an emulsion spray, etc., and application using a roller brush, a rubber rake, etc.
[0066] When the cationic asphalt emulsion composition according to the present disclosure is used, adhesion of asphalt to vehicle tires can be suppressed to a low level even when sprayed using a distributor. In addition, the cationic asphalt emulsion composition according to the present disclosure is less likely to generate aggregates, so that the workability during the spraying or application is good.
[0067] The amount of the cationic asphalt emulsion composition according to the present disclosure to be sprayed or applied is not particularly limited and may be within a known range. In the case of a tack coat, for example, 0.3 to 0.6 L / m, depending on the asphalt concentration in the composition. 2 In the case of a prime coat, for example, 1 to 2 L / m 2 It may be to some extent.
[0068] (Coat layer) The coating layer of the present disclosure is formed from the cationic asphalt emulsion composition. For example, the cationic asphalt emulsion composition according to the present disclosure is sprayed or applied, cured, and a coating is formed to form a coating layer mainly composed of asphalt. The thickness of the coating layer is not particularly limited and may be appropriately determined in consideration of the performance, but may usually be within the range of 0.1 to 10 mm. The coating layer is preferably a tack coat layer or a prime coat layer, and is particularly preferably a tack coat layer.
[0069] (Method of applying a coating layer using an anionic decomposer) As described above, the cationic asphalt emulsion composition according to the present disclosure can form a coating layer by spraying or applying it to an object, and the method of applying the coating layer is preferably a method in which it is combined with an anionic decomposer. Specifically, a method including a step of spraying or applying the cationic asphalt emulsion composition and the anionic decomposer to a surface to be applied so that the cationic asphalt emulsion composition and the anionic decomposer come into contact with each other is preferable, and in particular, a method including a step of spraying or applying the anionic decomposer immediately after spraying or applying the cationic asphalt emulsion composition to the object is more preferable.
[0070] The method of spraying or applying the anionic decomposer is not particularly limited and can be any known method. As with the cationic asphalt emulsion composition, examples of the method include spraying using a sprayer such as a distributor (a vehicle for spraying asphalt emulsion) or an engine sprayer, a watering can, an emulsion spray, etc., and application using a roller brush, rubber rake, etc.
[0071] By spraying or applying the anionic decomposer so that the cationic asphalt emulsion composition according to the present disclosure and the anionic decomposer come into contact with each other, the cationic emulsifier in the asphalt emulsion and the polymer particles can be decomposed, and an asphalt coating can be formed immediately. The anionic decomposer is not particularly limited, but examples thereof include sodium hydroxide, and alkali metal salts of sulfonic acid, phosphoric acid, and tripolyphosphoric acid. These alkali metal salts include organic salts consisting of organic substances such as naphthalenesulfonic acid-formaldehyde condensates, partial alkyl esters of polycarboxylic acids, and alkylsulfonic acids and alkali metals, and inorganic salts consisting of inorganic substances such as sodium polyphosphate and alkali metals.
[0072] The cationic asphalt emulsion of the present disclosure, since the emulsifier contained in the polymer particles is composed only of a cationic emulsifier, when used in combination with an anionic decomposer, can particularly effectively separate (decompose) asphalt from water, and can particularly shorten the construction period using the decomposer after asphalt construction.
[0073] (Method of construction of asphalt pavement using anionic decomposition agents) The asphalt pavement construction method of the present disclosure includes a step of providing a coating layer by the coating layer construction method, and a step of providing an asphalt mixture layer on the surface of the coating layer.
[0074] A specific example of the step of providing the asphalt mixture layer is a method in which the heated asphalt mixture or the cold asphalt mixture is spread evenly on the surface of the coating layer, pressure is applied to make it flat, and then the mixture is cured. However, as described above, the heated asphalt mixture is limited to one that has a temperature that does not exceed the glass transition temperature of the polymer particles contained therein after heating and application.
[0075] The following items enumerate preferred aspects of the present disclosure, but the present invention is not limited to the following items. [Item 1] A cationic asphalt emulsion additive comprising: The additive comprises polymer particles, The polymer particles contain an emulsifier and an acrylic rubber, The emulsifier is an additive consisting of only a cationic emulsifier. [Item 2] 2. The additive according to item 1, wherein the cationic asphalt emulsion is used in combination with an anionic breaker. [Item 3] The polymer particle includes a core layer and a shell layer located outside the core layer, the core layer is made of the acrylic rubber, 3. The additive according to claim 1 or 2, wherein the shell layer is formed from a non-crosslinked polymer. [Item 4] 4. The additive according to item 3, wherein the non-crosslinked polymer has a glass transition temperature of 50° C. or higher. [Item 5] 5. The additive according to any one of items 1 to 4, wherein the cationic emulsifier is an emulsifier containing alkyltrimethylammonium chloride. [Item 6] 6. The additive according to any one of items 1 to 5, wherein the content of the acrylic rubber in the polymer particles is 30 to 80% by weight. [Item 7] 4. The additive according to item 3, wherein the content of the core layer in the polymer particle is 30 to 80% by weight. [Item 8] 8. The additive according to any one of items 1 to 7, wherein the polymer particles have a volume average particle size of 80 to 500 nm. [Item 9] 9. The additive according to any one of items 1 to 8, wherein the additive is a latex of the polymer particles. [Item 10] A cationic asphalt emulsion and the additive according to any one of items 1 to 9, The cationic asphalt emulsion composition includes asphalt, water, and a cationic emulsifier. [Item 11] Item 11. The cationic asphalt emulsion composition according to item 10, wherein the content of the additive in the cationic asphalt emulsion composition is 1 to 50 parts by weight in terms of the solid content of the polymer particles relative to 100 parts by weight in terms of the solid content of the cationic asphalt emulsion. [Item 12] The method includes a step of mixing a cationic asphalt emulsion and the additive according to any one of items 1 to 9, The thione asphalt emulsion contains asphalt, water, and a cationic emulsifier, [Item 13] Item 12. A coating layer formed from the cationic asphalt emulsion composition according to item 10 or 11. [Item 14] Item 14. The coating layer according to item 13, wherein the coating layer is a tack coat layer. [Item 15] Item 12. A method for applying a coating layer, comprising the steps of spraying or applying the cationic asphalt emulsion composition and the anionic decomposer according to Item 10 or 11 to a surface to be applied so that the cationic asphalt emulsion composition and the anionic decomposer are in contact with each other. [Item 16] A step of spraying or applying the cationic asphalt emulsion composition and the anionic decomposer to a surface to be treated so that the cationic asphalt emulsion composition and the anionic decomposer are in contact with each other to provide a coating layer; and A method for constructing an asphalt pavement, comprising the step of providing an asphalt mixture layer on the surface of the coating layer. EXAMPLES
[0076] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following, unless otherwise specified, "parts" means "parts by weight" and "%" means "% by weight".
[0077] Example 1 (Formation of the core layer) 2900 g of deionized water and 32.0 g of Catiogen TML (30% lauryl trimethyl ammonium chloride, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) were charged into an 8 L polymerization reactor, the temperature was raised to 65° C., and nitrogen was flowed into the reactor. 150 g (5 parts) of butyl acrylate and 0.375 g (0.01 parts) of allyl methacrylate were added to the polymerization reactor, and 3.0 g of an azo initiator V-50 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.: 2,2'-azobis(2-methylpropionamidine) dihydrochloride) adjusted to 10% was added, and the mixture was stirred for 30 minutes. 30.0g of azo initiator V-50 adjusted to 10% was added, and a mixture of 1500g (50 parts) of butyl acrylate, 3.75g (0.13 parts) of allyl methacrylate, and 78.0g of Catiogen TML were added to the polymerization machine over 120 minutes. 30 minutes after the addition was completed, 60.0g of azo initiator V-50 adjusted to 10% was added and stirred for 30 minutes. As a result, a latex containing acrylic rubber particles was obtained.
[0078] (Shell layer formation) A mixture of 1260g (42 parts) of methyl methacrylate and 90g (3 parts) of styrene was added to the polymerizer over 110 minutes. 30 minutes after the addition was completed, 30.0g of azo initiator V-50 adjusted to 10% was added and stirred for 30 minutes. As a result, a latex of acrylic rubber-containing polymer particles with a core-shell structure having a polymerization conversion rate of 100%, a solid content concentration of 50.2%, and a volume average particle diameter of 220nm was obtained.
[0079] (Examples 2 to 6) A latex of acrylic rubber-containing polymer particles having a core-shell structure was obtained in the same manner as in Example 1, except that the type or amount of monomer was changed according to the description in Table 1 or 2.
[0080] Comparative Example 1 (Formation of the core layer) 2730 g of deionized water and 5.0 g of EMAL 2FG (Kao Corporation: sodium lauryl sulfate solid content, 30%) were charged into an 8 L polymerization reactor, the temperature was raised to 50° C., and nitrogen was flowed into the reactor. A mixture of 150 g (5 parts) of butyl acrylate, 0.375 g (0.01 parts) of allyl methacrylate, and 0.3 g of t-butyl hydroperoxide (solid content 69%) was added to the polymerization reactor, a solution of 0.00864 g of ferrous sulfate (FeSO4·7H2O) and 0.03456 g of disodium ethylenediaminetetraacetate dissolved in 8.6 g of deionized water was added, and 48.0 g of sodium formaldehyde sulfoxylate (solid content 5%) was added, and the mixture was stirred for 30 minutes.
[0081] 4.7g of EMALE 2FG (Kao Corporation: sodium lauryl sulfate, solid content 30%) was added, and a mixture of 1650g (55 parts) of butyl acrylate, 4.125g (0.14 parts) of allyl methacrylate, 27.0g of Phosphanol RD-510Y (Toho Chemical Industry Co., Ltd.: polyoxyethylene lauryl ether phosphate), and 3.0g of t-butyl hydroperoxide (solid content 69%) was added to the polymerization machine over 165 minutes. At the end of the addition, 3.0g of t-butyl hydroperoxide (solid content 69%) was added and stirred for 30 minutes. As a result, a latex containing acrylic rubber particles was obtained.
[0082] (Shell layer formation) 60.0 g of sodium formaldehyde sulfoxylate (solid content 5%) was added to the polymerization reactor. A mixture of 1050 g (35 parts) of methyl methacrylate, 60 g (2 parts) of styrene, 90 g (3 parts) of polyethylene glycol monomethacrylate (n=4.5, product name: Blenmar PE-200, manufactured by NOF Corporation), and 3.3 g of t-butyl hydroperoxide (solid content 69%) was added to the polymerization reactor over 120 minutes.
[0083] Sodium formaldehyde sulfoxylate and t-butyl hydroperoxide were added appropriately, and polymerization was completed after 80 minutes. Then, 10.5 g of Emulgen LS-110 (Kao Corporation: polyoxyethylene polyoxypropylene alkyl ether) was added to the latex to obtain a latex of acrylic rubber-containing polymer particles with a core-shell structure having a polymerization conversion rate of 99.8%, a solid content concentration of 50.0%, and a volume average particle diameter of 230 nm.
[0084] Comparative Example 2 (Formation of the core layer) 10 g of disodium hydrogen phosphate (10% solids content) was added to 90 g of deionized water, and then a solution of 0.237 g of ferrous sulfate (FeSO4 7H2O) and 0.395 g of disodium ethylenediaminetetraacetate in 125.8 g of deionized water was added, and deoxidization was carried out at -0.01 MPa for 15 minutes. 2,668 g of Neopelex G-15 (Kao Corporation: sodium dodecylbenzenesulfonate solid content 15.0%), 16,500 g (49.5 parts) of butadiene, 3,500 g (10.5 parts) of styrene, and 150 g of t-dodecyl mercaptan were placed in a 100 L pressure-resistant autoclave, and the internal temperature was raised to 50°C.
[0085] 140.0 g of sodium formaldehyde sulfoxylate (solid content 5%) and 7.7 g of paramenthane hydroperoxide (solid content 52%) were added to initiate polymerization.
[0086] 15 hours after the start of the polymerization, the mixture was degassed under reduced pressure to remove the butadiene remaining without being used in the polymerization, thereby terminating the polymerization. A latex having a solid content of 45.0% was obtained.
[0087] During the polymerization, sodium formaldehyde sulfoxylate, paramenthane hydroperoxide, ferrous sulfate (FeSO4·7H2O) and disodium ethylenediaminetetraacetate were added to a 100L pressure autoclave in arbitrary amounts and at arbitrary times. As a result, a latex containing styrene-butadiene rubber particles was obtained.
[0088] (Shell layer formation) 2000 g of the obtained rubber latex (solid content 45.0%) was charged into an 8 L polymerization machine, and the shell layer was polymerized in the same manner as in Comparative Example 1 thereafter to obtain a latex of styrene-butadiene rubber-containing polymer particles having a core-shell structure with a polymerization conversion rate of 99.6%, a solid content concentration of 49.8%, and a volume average particle diameter of 170 nm.
[0089] (Polymerization conversion rate) A part of the obtained latex was sampled and weighed, and dried in a hot air dryer at 120℃ for 1 hour. The weight after drying was weighed as the solid content. The ratio of the weighing results before and after drying was calculated as the solid content ratio in the latex. Finally, the polymerization conversion rate was calculated by the following formula using this solid content ratio. Formula: Polymerization conversion rate = [(total weight of raw materials charged x solid component ratio - total weight of raw materials other than monomers) / weight of charged monomer] x 100 (%)
[0090] (glass transition temperature Tg of shell layer) The glass transition temperature Tg of the non-crosslinked polymer of the shell layer was calculated using the above FOX equation.
[0091] (Volume average particle size) The volume average particle size of the polymer particles was measured in the state of the polymer particle latex. The measuring device used was Nanotrac Wave manufactured by Nikkiso Co., Ltd. The calculation mode was set to the UPA compatible mode.
[0092] (Evaluation method) The polymer particle latex obtained in each of the Examples and Comparative Examples was used to carry out the following evaluations. In Reference Examples 1 and 2, the polymer particle latex was not added, and only the asphalt emulsion was used to carry out each evaluation.
[0093] (Evaluation of the presence or absence of aggregates) The asphalt emulsion and polymer particle latex were mixed with a wooden spatula for 1 minute in the following ratio to obtain an asphalt emulsion composition. The emulsion composition was passed through a 32 mesh SUS plain weave wire net, and if no agglomerates were found on the wire net by visual inspection, it was judged as "absent", and if they were found, it was judged as "present". Asphalt emulsion AE: Cationic asphalt emulsion for tack coat (PK-4, solid content: 60%), or cationic asphalt emulsion for tire adhesion suppression tack coat (PKM-T, solid content: 60%) Polymer particle latex Lx: Polymer particle latex obtained in each Example or Comparative Example (solid content concentration: 50%) When AE is PK-4: AE=10.5g, Lx=4.5g (AE / Lx=70% / 30%, AE(solid content) / Lx(solid content)=100 parts / 43 parts) When AE is PKM-T: AE = 12.75 g, Lx = 2.25 g (AE / Lx = 85% / 15%, AE (solid content) / Lx (solid content) = 100 parts / 17.6 parts)
[0094] (Asphalt adhesion (tire adhesion) suppression evaluation) In order to evaluate the effect of adding polymer particle latex to asphalt emulsion on inhibiting adhesion of asphalt to tires, the adhesion rate to a rubber sheet at 60°C was measured using a wheel tracking tester (manufactured by Iwata Kogyosho Co., Ltd.).
[0095] First, the asphalt emulsion AE and the polymer particle latex Lx were mixed in a ratio of AE:PK-4 / Lx=70% / 30% or AE:PKM-T / Lx=85% / 15% to prepare an asphalt emulsion composition.
[0096] Next, the asphalt emulsion composition was applied to a slate board (classified as a soft board according to JIS A 5430 fiber-reinforced cement board) measuring 300 mm in length, 300 mm in width, and 3 mm in thickness at a solid content of 300 g / m 2 The asphalt emulsion composition was left to cure at room temperature until it was completely decomposed, to prepare a test specimen.
[0097] The material of the rubber sheet was natural rubber, and the rubber hardness was JIS hardness 84±4 at 20°C and 78±2 at 60°C. The rubber sheet was 1 mm thick and molded into a strip (length 300±10 mm, width 60±3 mm). The tire adhesion rate was measured by a wheel tracking test according to the following procedures (1) to (7). (1) The prepared specimen and the molded rubber sheet are cured in a thermostatic chamber adjusted to 60±1°C for at least 4 hours. (2) Measure the weight of the rubber sheet immediately before the test. (3) Place the rubber sheet on the part of the test specimen where the tire runs, and move the tire back and forth once with a load of 624±10N. (4) After the tire has been driven, the rubber sheet is peeled off vertically with a constant force within 2 seconds. (5) The weight of the rubber sheet is immediately measured to determine the weight of the adhered asphalt coating. (6) The above steps (1) to (5) shall be carried out at least three locations per test specimen. (7) Tire adhesion rate is calculated using the following formula. Tire adhesion rate (wt%) = [rubber sheet weight after test (g) - rubber sheet weight before test (g)] / [tire running area (m 2 ) × emulsion composition solids coating amount (g / m 2 )] x 100
[0098] (Evaluation of decomposition effect by decomposition agent) The decomposition effect of a decomposer on asphalt emulsion was evaluated. Asphalt emulsion AE and polymer particle latex Lx were mixed in a ratio of AE:PK-4 / Lx=70% / 30% or AE:PKM-T / Lx=85% / 15% to prepare an asphalt emulsion composition.
[0099] 20 mL of the asphalt emulsion composition (each Example and Comparative Example) and Asphalt Emulsion AE (each Reference Example) were measured and uniformly spread in a petri dish with a diameter of 10 cm. 3 mL of a 3 wt % aqueous solution of sodium tripolyphosphate was added thereto as an anionic decomposer and quickly mixed. It was visually confirmed whether gelation occurred and whether the liquid flowed when the petri dish was tilted. If gelation occurred and the liquid did not flow when the petri dish was tilted, the effect of the decomposer was judged to be "present", and if gelation did not occur or the liquid flowed when the petri dish was tilted, the effect of the decomposer was judged to be "absent".
[0100] The results of the evaluation described above are shown in Tables 1 and 2. Table 1 shows the evaluation results when PK-4 was used as the cationic asphalt emulsion, and Table 2 shows the evaluation results when PKM-T was used as the cationic asphalt emulsion.
[0101] [Table 1]
[0102] [Table 2]
[0103] From Tables 1 and 2, it can be seen that the polymer particles of Examples 1 to 6, in which the emulsifier was composed only of a cationic emulsifier, did not aggregate when added to an asphalt emulsion, exhibited the effect of inhibiting asphalt adhesion, and also had the effect of a decomposer.
[0104] On the other hand, the polymer particles of Comparative Example 1, in which the emulsifier was anionic or nonionic, did not agglomerate when added to the asphalt emulsion and exhibited the effect of inhibiting asphalt adhesion, but had no decomposition effect. Similarly, the polymer particles of Comparative Example 2 agglomerated when added to the asphalt emulsion, and had no decomposition effect.
[0105] From the above results, it is clear that the addition of acrylic rubber-containing polymer particles composed only of a cationic emulsifier to an asphalt emulsion suppresses asphalt adhesion after construction, makes it difficult for agglomerates to form in the emulsion, and also has the effect of acting as a decomposer.
Claims
1. A cationic asphalt emulsion additive comprising: The additive comprises polymer particles, The polymer particles contain an emulsifier and an acrylic rubber, The emulsifier is an additive consisting of only a cationic emulsifier.
2. 2. The additive of claim 1, wherein the cationic asphalt emulsion is used in combination with an anionic breaker.
3. The polymer particle includes a core layer and a shell layer located outside the core layer, the core layer is made of the acrylic rubber, The additive of claim 1 or 2, wherein the shell layer is formed from a non-crosslinked polymer.
4. The additive according to claim 3, wherein the non-crosslinked polymer has a glass transition temperature of 50°C or higher.
5. The additive according to claim 1 or 2, wherein the cationic emulsifier is an emulsifier containing alkyltrimethylammonium chloride.
6. The additive according to claim 1 or 2, wherein the content of the acrylic rubber in the polymer particles is 30 to 80% by weight.
7. The additive according to claim 3, wherein the content of said core layer in said polymer particle is 30 to 80% by weight.
8. The additive according to claim 1 or 2, wherein the polymer particles have a volume average particle size of 80 to 500 nm.
9. The additive according to claim 1 or 2, wherein the additive is a latex of the polymer particles.
10. A cationic asphalt emulsion and the additive of claim 1, The cationic asphalt emulsion composition includes asphalt, water, and a cationic emulsifier.
11. The cationic asphalt emulsion composition according to claim 10, wherein the content of the additive in the cationic asphalt emulsion composition is 1 to 50 parts by weight in terms of the solid content of the polymer particles per 100 parts by weight in terms of the solid content of the cationic asphalt emulsion.
12. The method comprises the steps of: mixing a cationic asphalt emulsion and the additive according to claim 1 or 2; The thione asphalt emulsion contains asphalt, water, and a cationic emulsifier,
13. A coating layer formed from the cationic asphalt emulsion composition according to claim 10 or 11.
14. The coating layer of claim 13 , wherein the coating layer is a tack coat layer.
15. A method for applying a coating layer, comprising the steps of spraying or applying the cationic asphalt emulsion composition and the anionic decomposer described in claim 10 or 11 to a surface to be applied so that the cationic asphalt emulsion composition and the anionic decomposer are in contact with each other.
16. A step of forming a coating layer by spraying or applying the cationic asphalt emulsion composition and the anionic decomposer on a surface to be treated so that the cationic asphalt emulsion composition and the anionic decomposer according to claim 10 or 11 are in contact with each other; and A method for constructing an asphalt pavement, comprising the step of providing an asphalt mixture layer on the surface of the coating layer.
Citation Information
Patent Citations
Dispersion type surface treatment construction method
JP2000336602A
Modified asphalt composition, hardened film using the same, and waterproofing method
JP2010174229A